ANALISIS PENERAPAN SAK ETAP PADA BADAN USAHA MILIK DESA (BUMDes) (Studi Kasus Pada Badan Usaha Milik Desa Bersama (BUMDesMa) Bagus Desa Pandesari Kecamatan Pujon Kabupaten Malang) - Sofyan Sauri; Moh. Amin; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Badan Usaha Milik Bersama (BUMDesMa) is a business entity that is expected to be able to assist residents in meeting the needs of villagers, and is also accepted as a business opportunity or to increase employment and increase knowledge of rural residents, and also as a forum for rural community economic activities. So that Badan Usaha Milik Desa Bersama (BUMDesMa) is obliged to present open financial reports in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This research has the aim of looking at the application of the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the presentation of the financial statements of Badan Usaha Milik Desa Bersama (BUMDesMa) Bagus. The type of this research is a qualitative descriptive method and only describes the results of interviews conducted at Badan Usaha Milik Desa Bersama (BUMDesMa) Bagus. From this study, the researchers found that Badan Usaha Milik Desa Bersama (BUMDesMa) Bagus had implemented the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP).Keywords: SAK ETAP, BUMDesMa